Internet connectivity disruption in Zambia (Zambia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Zambia. Data sourced from IODA.
Network Disruption Incident ID: ZM-2026-0005. Severity: critical. Confidence: 67%